STUDENTS’ PERCEPTION TOWARD TOEFL PREDICTION TEST AS ONE OF THE GRADUATION REQUIREMENTS FROM UNIVERSITY - Zakiah, Azra; Dahnilsyah; Masyhur (International Journal of Educational Best Practices, 2023)
The students at the university under investigation are required to successfully complete the TOEFL Prediction test in order to be eligible for graduation. This study was conducted to assess the perceptions of these students regarding the TOEFL Prediction test as  one of the graduation requirements. The research employed a descriptive-quantitative methodology and involved 171 English Study Program students from three different academic batches. A questionnaire served as the primary instrument for data collection, with data analysis carried out using Microsoft Excel and SPSS statistics version 26. The results of the data analysis indicated that the mean scores for most items in the questionnaire were in the high range. Specifically, 25 out of the 29 questionnaire items obtained mean scores above 3.40, demonstrating that students' perceptions in this study leaned positively toward the TOEFL Prediction test policy. However, it's important to note that nearly half of the students recognized that the TOEFL Prediction test is not an easy test. Furthermore, there is room for improvement in terms of students' understanding of the type of TOEFL test provided by the language centre at the university and the benefits of the TOEFL certificate. These findings can provide valuable input for the university's policymakers and administrators. They can use this information to design new initiatives and strategies aimed at assisting students in improving their test-taking skills and their understanding of the TOEFL Prediction test's structure. Such efforts can contribute to enhancing students' overall readiness for this requirement.